Analisis Penggunaan Media Digital Interaktif Untuk Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Matematika DI Sekolah Dasar - Ronalita Simorangkir; Rina Sinaga; Romasda Limbong; Zaira Nazwa (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2023)
The very rapid development of technology has various positive impacts on human life, especially in the field of education. The aim of this research is: This research aims to explain the use of interactive learning media which can influence the learning outcomes of elementary school students. This research is qualitative research in the nature of a library study by examining trusted sources either in written form or in relevant digital format without going directly to the field. Based on a literature review analysis of several scientific articles, it was found that the use of digital learning media can improve the learning outcomes of elementary school students.Keywords: digital media, elementary school